Assessment of the Genetic Variability, Heritability, and Genetic Advance for Seed Yield and its Related Traits in Fennel (Foeniculum vulgare Mill.) - Yadav, Preeti; Ram, C. N.; Yadav, Garima; Kannaujiya, Amit Kumar; Kumar, Subham; Kumar, Ankur (International Journal of Bio-resource and Stress Management, 2026)
The experiment was conducted during the rabi season of 2020–2021 at NDUAT, Kumarganj, Ayodhya (U.P.), to assess genetic variability, heritability and genetic advance for seed yield and its related traits in fennel. A total of 78 genotypes, along with three checks, were studied for 12 quantitative characters. Analysis of variance revealed that the variances due to checks were highly significant for all characters except internodal length and nodes plant-1. Similarly, the variance due to blocks was highly significant for traits such as number of umbels plant-1, number of umbellate umbel-1, number of seeds umbellate-1, umbel diameter, plant height, seed yield plant-1, suggesting considerable environmental influence on these traits. The highest phenotypic and genotypic coefficients of variation were recorded for number of umbels plant-1 (22.25%, 22.10%), respectively. High estimates of broad-sense heritability were observed for days to 50% flowering (99.64%), number of umbels plant-1 (98.66%), number of umbellate umbel-1 (97.46), umbel diameter (97.22), number of branches plant-1 (96.45%), nodes plant-1 (96.22%), 1000-seed weight (92.45) and inter nodal length (83.26%). The highest genetic advance was observed for the number of umbels plant-1 (26.86), which also showed the highest genetic advance as % of mean (45.28%), followed by umbel diameter (33.50%).The results indicated that selection based on these traits would be effective for improving seed yield in fennel.